Analisis Toksisitas Akut LC50-96 Jam Limbah Laundri Terhadap Ikan Mujair (Oreochromis sp.) - Nur Azizah Kartikasari; Dedy Suprayogi; Amrullah Amrullah (Fakultas Teknik, 2022)
Laundry waste is one of the wastes that is wasted when it is disposed of continuously and continuously. This results in the destruction of aquatic ecosystems, especially fish. This study aims to determine the value of LC50-96 hours of laundry waste on tilapia fish (Oreochromis sp.). This study begins by knowing the parameters of BOD, COD, TSS, NH3, and detergent at the stage of Range Finding Test and Acute Toxicity Test. In addition, pH, temperature, and DO parameters were also tested every day. After that, acclimatization was carried out for 7 days without feeding the fish. Then continued with the range Finding test stage for 96 hours with variations of 0% (control), 5%, 10%, 20%, 40%, 60%, 80%, and 100%. The range obtained in the range Finding test stage is 20%. So that the variations in the acute toxicity test stageused include 6%, 9%, 12%, 15%, and 18%. After observing fish mortality approaching 50%, then these results were analyzed using Microsoft Excel. The LC50 value obtained in this test is 60002,5.